A COMPARATIVE STUDY OF EARLY AND LATE SASSANIAN COINAGE - Vollgraaff, Stephanus (Journal for Semitics, 2017)
Sassanian coinage is one the best sources for information on the individual kings from this Persian dynasty. This is because the coins are primary sources that are unaltered. The way in which the Sassanian coins changed is not a topic that has been dealt with extensively.1 A stylistic analysis and comparison of the coins from the different Sassanian ages will be done. In this study the coins from the Sassanian rulers of the early period (224–302 C.E.) and the late period (628–652 C.E.) will be analysed for stylistic characteristics that differentiated them from other Sassanian coins. Trends that were common to coins from each period will be identified as well so that the continuity and breaks in coin design from each period can be illustrated and compared. The factors behind some rulers following the standards set by predecessors and others reinventing it will be exposed by the study.